Perception of Employees on Lean Six Sigma Practices and Corporate Sustainability in Automotive Manufacturing Industry - Nur Syahirah, Mohamad Azlan; Noraini, Mohd Razali (Springer Singapore, 2023)
This study aims to examine the perception of employees in the Malaysian automotive industry towards their company regarding the level of awareness in the implementation of Lean Six Sigma (LSS) and corporate sustainability. Two sets of questionnaires each containing two sections were developed in this survey. Surveys were given to Top Management and Executive positions, and Shop Floor employees. The evaluation method is generally in the form of a Five-Point Likert Scale Questionnaire. The targeted respondents were employees from three different automotive manufacturing companies. The data obtained was analyzed using Minitab. The results show a good perception of the implementation of LSS and awareness of corporate sustainability among employees in the automotive sector. However, the study revealed that no correlation between LSS practices and the sustainability awareness in companies where high LSS implementation will not affect corporate sustainability awareness. Findings from this study also revealed that the environmental aspect is the most impacted by LSS practices. There is also a correlation between the positions and the level of awareness in LSS implementation and sustainability performance in which the upper management shows a better awareness towards the practices compared to Shop Floor employees. In general, employees in automotive sector do have good perception on LSS implementation and corporate sustainability awareness. This will reinforce the culture of sustainability awareness among the engineers and encourage them to think on sustainability ideas during the concept and design stages of product development.